(untitled) (Research, Society and Development, 2020)
Traffic accidents are important causes of morbidity and mortality, representing the main cause of death among people aged 15 to 29 years. Most of the injuries caused by these accidents are preventable, because of this, these events require policies and strategies aimed at preventing traffic injuries. Health education is a central tool in this process, as it provides awareness and transformation of individuals. The extension project Extension project “safe traffic: preventing trauma through education” aimed to promote the prevention of traffic accidents in the municipality of Parnaíba - PI, through the execution of educational activities with children and adolescents. The project was applied by 18 medical students from the Federal University of Vale do Parnaíba and the Higher Education Institute of Vale do Parnaíba, members of the Academic League of Trauma, Urgency and Emergency (LATURE). In this sense, considering that traffic accidents are a major public health problem in Brazil, it can be said that preventive actions against these traumas, especially inserted in a playful way and approached in a practical way, are very useful in learning concerning Cheers. As it happened, the educational objectives were achieved and the project had a positive impact on the target audience.